Proof Without Words: Trisection of a Parallelogram’s Diagonal (p. 58) - Oxman, Victor; Stupel, Moshe (Ohio Journal of School Mathematics, 2020)
Given a parallelogram ABCD, E and F are the midpoints of AB and CD. H, I are the points of intersection of diagonal BD with lines EC and AF. Then BH=HI=ID.